Natural Ventilation: Planning Design Guidelines for Residential High-rises - Tantasavasdi, Chalermwat; Jareemit, Daranee (Journal of Architectural/Planning Research and Studies (JARS), 2005)
This paper presents the study of natural ventilation as a mean to replace air-conditioning system for planning design of residential high–rises in Bangkok. Method includes simulation by Computational Fluid Dynamics program on two types of building: double–loaded corridor and point-blocked corridor; and two types of corridor openings: directly opposite openings and adjacent openings. It is discovered that natural ventilation can be used in residential high–rises in Bangkok to achieve human comfort level. Building plans with directly opposite corridor openings and their orientation that block the wind have best efficiency for natural ventilation as each room has better ventilation. It is also found that the mean velocity in the rooms at the back of a building is reversal to its height. The findings from this research lead to residential high–rise design guidelines that promote natural ventilation.